Correlation between acute ischaemic stroke clot length before mechanical thrombectomy and extracted clot area: Impact of thrombus size on number of passes for clot removal and final recanalization. (September 2021) - Rossi, Rosanna; Fitzgerald, Seán; Gil, Sara M; Mereuta, Oana M; Douglas, Andrew; Pandit, Abhay; Brennan, Paul; Power, Sarah; Alderson, Jack; O'Hare, Alan; Gilvarry, Michael; McCarthy, Ray; et al.
Introduction: We assessed the correlation between thrombus size before and after mechanical thrombectomy, measured as length by Computed Tomography Angiography/Non-Contrast Computed Tomography (CTA/NCCT) and Extracted Clot Area, ECA, respectively. We also assessed the influence of thrombus size on the number of passes required for clot removal and final recanalization outcome. Materials and methods: Acute ischaemic stroke (AIS) thrombi retrieved by mechanical thrombectomy from 500 patients and data of clot length by CTA/NCCT were collected from three hospitals in Europe. ECA was obtained by measuring the area of the extracted clot. Non-parametric tests were used for data analysis. Results: A strong positive correlation was found between clot length on CTA/NCCT and ECA (rho = 0.619, N = 500, P < 0.0001*). Vessel size influences clot length on CTA/NCCT (H2 = 98.6, P < 0.0001*) and ECA (H2 = 105.6, P < 0.0001*), but the significant correlation between CTA/NCCT length and ECA was evident in all vessels. Poorer revascularisation outcome was associated with more passes (H5 = 73.1, P < 0.0001*). More passes were required to remove longer clots (CTA/NCCT; H4 = 31.4, P < 0.0001*; ECA; H4 = 50.2, P < 0.0001*). There was no significant main association between recanalization outcome and length on CTA/NCCT or ECA, but medium sized clots (ECA 20–40 mm 2 ) were associated with least passes and highest revascularisation outcome (N = 500, X 2 = 16.2, P < 0.0001*). Conclusion: Clot length on CTA/NCCT strongly correlates with ECA. Occlusion location influences clot size. More passes are associated with poorer revascularisation outcome and bigger clots. The relationship between size and revascularisation outcome is more complex. Clots of medium ECA take less passes to remove and are associated with better recanalization outcome than both smaller and larger clots.